Integrating Renewable Energy, Storage, and Demand Management in Community Energy Systems: A Case Study of Trent Basin - Xu, Xinrui (International Journal of Electric Power and Energy Studies, 2025)
Community energy systems are considered a key means of achieving carbon neutrality at the local level. This paper evaluates the current and future energy systems of the Nottingham Trent Basin community, as a case study, and proposes strategies to reduce carbon emissions and enhance energy efficiency. Analyses of building energy demand, carbon emissions, and model accuracy were conducted based on simulation data from the IES model and measured electricity data from selected households. Results indicate that the community’s average domestic electricity consumption exceeds the UK national average, while natural gas consumption is significantly lower, suggesting progress in heating decarbonization. Further simulations demonstrate that a 200 kWp photovoltaic system could cover approximately 82% of annual electricity demand. Integrating this with a 2 MWh energy storage system could reduce annual carbon emissions by nearly 80%. Future analysis indicates that introducing air-source heat pumps could reduce heating- related emissions by approximately 71%, while expanding PV and storage capacity would further decrease grid dependency. Concurrently, the research evaluated electric vehicle integration and load management strategies, exploring time- series based electricity demand forecasting models. Findings indicate that smart community energy systems, by integrating renewable energy, electrified heating, and electric vehicle management, can significantly advance carbon reduction at the community level. This paper highlights the importance of combining technical measures with demand side management in achieving carbon neutrality.